Three Worlds of Collective Human Experience: Individual Life, Social Change, and Human Evolution - Shaw, Victor N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores three worlds shared by the humans in their collective experiences. It identifies and explores the world of commonsense, the world of religion, and the world of science as three essential dimensions of human experience. The book helps understand that humans can gain comfort and pleasure in commonsense, achieve meaning and purpose from religion, and attain truth and rationality through science. It actively applies theories to and develops theoretical explanations from different domains or situations of human existence. This book is of interest to theorists, researchers, instructors, and students across major academic disciplines in the humanities and social sciences.
Part 1: Three Worlds -- Chapter 1. The Commonsensical -- Chapter 2. The Religious -- Chapter 3. The Scientific -- Chapter 4. The General. - Part 2: Individual Life -- Chapter 5. Born to Commonsense -- Chapter 6. Reared in Religion -- Chapter 7. Educated with Science -- Chapter 8. Horizontal and Vertical Dimensions. - Part 3: Social Dynamics -- Chapter 9. Member Livelihood -- Chapter 10. Group Faith -- Chapter 11. Collective Development -- Chapter 12. Comparative and Historical Perspectives -- Part 4: Human Evolution -- Chapter 13. Ongoing Survival -- Chapter 14. Ultimate Destination -- Chapter 15. Universal Law -- Chapter 16. Spatial and Temporal Expanses.
Keywords: Social sciences -- Philosophy; Religion and sociology; Social history; Culture -- Study and teaching; Science -- Social aspects; Social Theory; Sociology of Religion; Social History; Cultural Studies; Science and Technology Studies